Initial approximation for Newton-Raphson iteration to calculate the neutral axis position of glulam bamboo - Irawati, Inggar Septhia (ASEAN engineering journal)
Glued laminated (glulam) bamboo has possibility to be used as construction material. For structural purpose, an analytical calculation is needed to estimate the structure capacity. As bamboo typicallyhas non linear material behavior under compression parallel to grain, it is essential to figure out thenon linear behavior of glulam bamboo for structural component.The research purpose is to figure out non linear behavior of glulam bamboo by determining maximum capacity under axial and lateral loadings according to actual properties of tension and compression parallel to grain. The failure load is numerically computed based on finite different method. A Newton-Raphson iterative procedure is employed to determine the deflection curve and neutral axis position that meet the equilibrium condition. Assumption used is that tensile or compressive stress is equal to zero when it is greater than its ultimate stress. This paper is focused to describe iterative procedure to obtain neutral axis position. The novelty of this study is the proposed initial approximation for iteration of neutral axis position which has never strongly been considered by previous study. Its application and detail discussion are presented. There are two reasons why initial approximation for obtaining neutral axis position is important to be understood. First, it influences the speed of convergence, and secondly, when the internal stress is close to the maximum strength, it might influence the convergence of calculation.